Guest Pro-Environmental Behavior of Save Energy in The Four Star Hotel Padang - Muhammad Daffa Valian Albar; Muhammad Ariq Alfarroz; Muhammad Fadlan Fahrezi; Feri Ferdian (Politeknik Bosowa, 2023)
The application of saving energy consumption must be given more attention as a form of concern for the environment. Currently, energy-saving behavior is being encouraged by business people, one of which is in the hotel industry. Guest behavior is very important in driving savings on hotel energy consumption, operational costs, and environmental issues. Promoting energy-saving behavior to guests is the right strategy to support and participate in energy-saving in the hospitality industry. This type of research is descriptive quantitative. The population in this study was 4,100 people and after being calculated by the Slovin formula, 98 samples were obtained. Research data was collected by questionnaire and processed using the PLS-SEM method. The purpose of this study was to determine the behavior of hotel guests in saving energy and to test three variables that influence pro-environmental behavior, namely habited culture, normative influence, and affective influence. The results obtained indicate that habitual culture has a significant positive effect on pro-environmental behavior. while normative influence and affective influence did not have a significant effect on pro-environmental behavior.